Optimal Location and Sizing of Thyristor Controlled Series Capacitor in Nigerian Transmission System Using Hippopotamus Optimization Algorithm - Okelola, Muniru Olajide; Oyedokun, Jelili Aremu; Adebiyi, Oluwaseyi Joseph; Oladejo, Azeez Opeyemi; Abiola, Johnson Opeyemi (Electrical Engineering and Technology, 2025)
Optimal power transmission plays a pivotal role in ensuring the stability and viability of the power grid, and such a need is further exacerbated by the rising power demands that developing power grids face. In this paper, a novel approach is presented to implement the Hippopotamus Optimization Algorithm (HOA) to ensure optimal Thyristor-Controlled Series Capacitor (TCSC) placement and size to reduce power transmission losses and improve voltage profile. A Newton-Raphson load flow study is developed to incorporate TCSC models, aiming to reduce active power losses and costs of generation. The results obtained on the IEEE 14-bus test network indicate the effectiveness of the proposed HOA method over the existing and manual methods. On the IEEE 14-bus test system, the proposed method was effective in reducing active power loss substantially from 13.599 MW to 4.101 MW and lowering the costs of the systems from $6799 to $2788. On the Nigerian 28-bus power grid, the HOA method successfully reduced the active power loss to 732.05 MW, compared to the value of 802.37 MW of active power loss on the base case. It was also successful in lowering the reactive power loss to 1655.58 Mvar, and the cost of operation was reduced to $372,541, outperforming the results obtained through the manual method. These results indicate that the HOA is a powerful strategy that can be employed to reduce active power loss substantially and improve the voltage stability without the need to develop extensive infrastructure.